Exploring reconfiguration of trends in CPUE to model sustainable TAC options for the pivotal YSLME anchovy fishery - Han, Qingpeng; Shan, Xiujuan; Jin, Xianshi; Gorfine, Harry (Frontiers in Marine Science, 2023)
Sustainable utilization of exploited fish stocks generally relies on characterizing key aspects of their population dynamics using mathematical models to evaluate their stock status. In this study, the Anchovy population (Engraulis japonicus) in the Yellow Sea large marine ecosystem (YSLME) was evaluated by using the ‘Just Another Bayesian Biomass Assessment’ (JABBA) model. Catch and the anchovy scientific survey biomass index data from 1989 to 2021 in its nominal or raw form, plus three adjusted CPUE trends using data acquired from the China Fishery Statistical Yearbook were each used to fit JABBA to explore the performance of reconfigured CPUE for setting a total allowable catch (TAC) quota to sustain the YSLME commercial anchovy fishery. Results showed contrasting trends in estimated biomass from the fishery independent surveys, and nominal and reconfigured commercial fishery CPUE, with the latter producing the most plausible results. The JABBA output based on the scientific survey biomass index indicated a 56.7% probability that the anchovy stock is currently healthy with 1.04 B2021/BMSY and 0.51 F2021/FMSY ratios, whereas JABBA estimates based on the nominal commercial CPUE-based were overly optimistic (100% probability stock was healthy). JABBA outputs based on the first two reconfigured CPUEs (Facpuey and FECcpuey) countered this overoptimism, with the survey biomass index-based assessment results lying between the extremes. This improvement in the modelled assessment was achieved because the reconfigured CPUE time series accommodated technological progress in fishing vessels and gear performance. Therefore, in instances where survey biomass index data are unavailable, we recommend using the two improved fishery CPUEs and combining the results of the two assessments to guide fishery management. Management reference points, however, should preferably be based on the more conservative of the two reconfigured CPUEs as a precautionary approach for setting a total allowable catch (TAC) whilst concomitantly considering the role of anchovy as prey for other economically important fish in the system.We encourage researchers to extensively review and improve the quality and availability of fisheries statistical data worldwide in the shared endeavour towards obtaining more realistic stock assessments.